Olive tree pruning as an agricultural residue for ethanol production. Fermentation of hydrolysates from dilute acid pretreatment - Díaz-Villanueva, M. J.; Cara-Corpas, C.; Ruiz-Ramos, E.; Romero-Pulido, I.; Castro-Galiano, E. (Spanish Journal of Agricultural Research, 2012)
The use of agricultural residues for ethanol production constitutes one of the most promising alternatives from an environmental point of view for substituting fossil fuels in the transport sector. This work deals with the fermentability of hydrolysates obtained from olive tree pruning biomass and the influence of the pH of the culture medium. Hydrolysates of olive tree biomass were obtained by dilute acid pre-treatment of the raw material at 180ºC and 1% (w/v) sulfuric acid concentration. After pretreatment, solid residue and liquid were separated by filtration. The liquid fraction (hydrolysate) was then submitted to detoxification (overliming) before being used as fermentation medium. Pichia stipitis and Pachysolen tannophilus were compared as fermenting microorganisms. Different initial pH values were also tested. The best results in terms of ethanol yield were obtained by P. tannophilus with values as high as 0.44 g ethanol g-1 sugar, and all liquids were fermented, to a different extent. P. stipitis could not ferment hydrolysates with initial pH below 6.5. It was also determined that ethanol production did not improve once glucose in the medium was totally converted, even if other sugars (xylose) were also consumed.